"If you want to understand something, try to change it": Social-psychological interventions to cultivate resilience. (2nd September 2015) - Brummelman, Eddie; Walton, Gregory M.
Abstract: We argue that social psychology has unique potential for advancing understanding of resilience. An exciting development that illustrates this is the emergence of social-psychological interventions – brief, stealthy, and psychologically precise interventions – that can yield broad and lasting benefits by targeting key resilience mechanisms. Such interventions provide a causal test of resilience mechanisms and bring about positive change in people's lives.